Aerial surveys of Murchison Falls Protected Area, Uganda, March 2010 - Rwetsiba, Aggrey; Nuwamanya, Edison (Pachyderm, 2020)
Murchison Falls Protected Area (MFPA)is the largest wildlife protected area in Uganda and forms one of the three sites that have been implementing the Monitoring the Illegal Killing of Elephants (MIKE) programme since 2002. A population survey of the MIKE site was conducted in March 2010 with the objective of establishing numbers of elephants and other medium and large mammals. The SRF method was used to determine wildlife distribution and numbers in MFPA. This method relies on counting within a systematically obtained sample (Norton-Griffiths 1978). The results of the survey indicate a general recovery and increase of major species, especially elephants, following a huge decline in numbers as a result of accelerated poaching that followed the breakdown of law and order in the 1970s and early 1980s. Despite the fact that various methods were used in previous surveys, some in dry seasons and others in wet seasons, the results still show general species recovery and significant population increase of certain species. Most of the species—namely elephant, Uganda kob, giraffe, warthog, buffalo, hartebeest and waterbuck—are steadily increasing. L’aire protégée des chutes de Murchison (MFPA) est la plus grande aire protégée de la faune en Ouganda et forme l’un des trois sites qui mettent en œuvre le programme du Système de suivi du braconnage des éléphants (MIKE) depuis 2002. Un recensement de la population du site de MIKE a été effectué en mars 2010 avec l’objectif d’établir le nombre d’éléphants et d’autres mammifères de taille moyenne et grande. On a utilisé la méthode du Vol de Reconnaissance Systématique pour déterminer la distribution de la faune et leur nombre dans la MFPA. Cette méthode repose sur le dénombrement au sein d’un échantillon obtenu systématiquement (Norton-Griffiths 1978). Les résultats de l’étude indiquent un recouvrement général et une augmentation des espèces majeures, surtout les éléphants, suite à un déclin énorme du nombre causé par le braconnage accéléré qui a suivi l’effondrement de l’ordre public dans les années 1970 et au début des années 1980. En dépit du fait qu’on a utilisé plusieurs méthodes dans les études antérieures, quelques-unes dans les saisons sèches et d’autres dans les saisons pluvieuses, les résultats montrent toujours un recouvrement général des espèces et une importante augmentation de la population de certaines espèces. La plupart des espèces à savoir, l’éléphant, le kob d’Ouganda, la girafe, le phacochère, le buffle, le bubale et le waterbuck augmentent régulièrement.